Measurement and structural modelling on factors of Islamic Fintech adoption among millennials in Malaysia - Rahim, Norafni @ Farlina; Bakri, Mohammed Hariri; Fianto, Bayu Arie; Zainal, Nurazilah; Al-Shami, Samer Ali Hussein (Emerald Group Holdings Ltd., 2022)
Purpose: This study aims to examine the results of structural equation modelling in applying unified theory of acceptance and use of technology in adopting Islamic Fintech among millennials in Malaysia via measurement and structural models. Design/methodology/approach: A total of 418 valid responses have been obtained from Malaysians who are using Islamic Fintech. Before the data is analysed into measurement and structural modelling preliminary analysis such as common method bias has been conducted. Findings: All the requirements for model fit in this study have been achieved. Four exogenous constructs are performance expectancy, effort expectancy, social influence and facilitating condition. The mediating construct is behavioural intention, whereas the endogenous variable is user adoption. All exogenous constructs show significant p-values except for effort expectancy. Practical implications: This study offers important implications, specifically for the digital economy that is currently making its way throughout every aspect of human life, namely, social, religious, financial transaction, entertainment and others. The impact of the digital economy can be traced through the emergence of Fintech. The adoption of Islamic Fintech is one of the least discussed areas academically, therefore, this study is considered necessary to explore the prediction of consumer behaviour in Islamic Fintech adoption as a part of the digital economy in Malaysia. Originality/value: This study fills the perceived gap in the existing financial technology literature by assessing Islamic financial technology adoption via measurement and structural modelling.